Progress towards economic consolidation - Karl Fasbender (Intereconomics, 1973)
Indonesia has dropped out of the news lately. The country which during the Sukarno era constantly made the headlines of the world press because of the spectacular foreign political actions of its headstrong president is now bending its energies on economic consolidation.
Keywords: 330; Indonesia